Picasso - Ormiston, Rosalind (Masters of art (Prestel Verlag), 2020)
"Pablo Picasso has long been considered the genius of modern art. His oeuvre is characterised by a diverse range of media and styles, including painting, drawing, printmaking, ceramics, and sculpture. During his long and celebrated career, Picasso was renowned as a master of reinvention who significantly influence and innovated art throughout the 20th century."--Back cover.